Treatment of Chronic Hepatitis C with High Dose Interferon Therapy Experience from Pertamina Central Hospital Jakarta - Waldemar Simanjuntak (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2002)
Background: Until several years ago, interferon alfa was the only drug with proven benefit for the treatment of chronic Hepatitis C. Several therapy categories such as fixed-dose regimens, induction-dose regimens and escalation-dose regimens are already known. With standard dose interferon therapy of 3 MU, TIW for 6 months, a sustained response rate can ve achieved in only 10-20% of patients. This study reports the Results of treatment of chronic Hepatitis C with high dose interferon therapy of 6 MU, TIW for 6 months. Methods: From February 1996 to February 1998, 15 patients with Hepatitis C were treated with interferon alfa-2b 6 MU, TIW for 6 months. Ultrasound-guided liver-biopsy was performed using the Menghini-Technique (Hepafix). Virological and biochemical responses were assessed at the end of the treatment period at week 24 and at the end of follow-up period at week 48 and up to 2 years later. Virological and biochemical sustained responses were defined as the absence of HCV-RNA, and SGPT concentration within the normal range at both weeks 24 and 48. Histological response was assessed after the end of treatment. Side-effects were observed and noted. Results: Ten out of 15 patients (66.7%) were HCV-RNA negative and 11 out of 15 patients (73.3%) demonstrated ALT within the normal range at week 24. At the end of the follow-up, from week 48 until 2 years later, HCV-RNA negative and normal ALT were found in 6 patients (40%). Histological improvement was found in 4 out of 6 patients. Fever was the most common side-effect and was found in 13 patients, while fatigue was found in 12 patients, myalgia in 11, headache in 10, and anorexia in 11 patients. Conclusion: High dose interferon alfa-2b therapy for the treatment of chronic Hepatitis C can improve the rate of sustained response, but is associated with more side-effects.   Key Words: Chronic hepatitis C, Interferon.